Innovative work behavior among teachers in Malaysia: the effects of teamwork, principal support, and humor / Aduni Johari, Nor Wahiza Abdul Wahat and Zeinab Zaremohzzabieh - Johari, Aduni; Abdul Wahat, Nor Wahiza; Zaremohzzabieh, Zeinab (Universiti Teknologi MARA, 2021)
The Fourth Industrial Revolution (Industry 4.0) gives impetus to educational reform. Education experts have recently recognized the benefits of using technology in learning and teaching. They believe that innovations will shape Education 4.0 and that teachers will need to be prepared to build creative learning environments that support student creativity. Thus, the main purpose of this paper is to examine the relationships between teamwork, principal support, humor, and innovative work behavior (IWB) among teachers. This study was conducted using a questionnaire, with a sample size of 354 school teachers in Malaysia. Multiple linear regression analysis has shown that teachers with high quality of teamwork and principal support were more likely to report innovative work behavior. The findings indicated that teachers who frequently use humor can create more innovative behavior. This paper can help managers and policymakers in the education sector, to develop a better understanding of these aspects, and their influence on teachers' innovative behavior at work. In doing so, it would be helpful if teachers learnt effective procedures for innovative behavior in class, via means of teamwork, humor, and principal support, to enhance their educational efforts. It is, therefore useful to establish university courses for pre-service teachers, focusing on new collaborative innovation strategies to encourage creativity and innovation in educational settings, and to apply collaborative creativity exercises in the classroom.